Quran Memorization in Madura: A Solution for Strengthening National Resilience in an Era of Social Change - Akh Syaiful Rijal; Bina Prima Panggayuh (IAIN Madura, 2026)
This study examines Qur’anic memorization education at PP. Bustanul Huffadz Assaidiyah Sampang, Madura, as a solution for strengthening national resilience in an era of social change through the genealogical approach of Michel Foucault. This study aims to examine Quran memorization as not only a process of memorizing the Quran, but also a medium for shaping disciplined, religious, and productive students. This research employs a qualitative method through library research and observation of Madurese pesantren traditions. The findings reveal three forms of power operating within tahfidz education. First, the pastoral power of the kiai instills religious values, nationalism, love for the homeland, and environmental awareness. Second, pesantren discipline through memorization deposits and communal control forms students who are orderly, responsible, and socially resilient. Third, pesantren biopower regulates students’ daily lives and learning patterns, producing healthy and productive generations. The study also finds that Qur’anic memorization education contributes to the achievement of Sustainable Development Goals (SDGs), particularly in education, social development, and environmental awareness. Therefore, the tahfidz tradition in Madura can be understood as a soft infrastructure that strengthens ideological, social, economic, and cultural resilience in supporting Indonesia Emas 2045 amid contemporary social transformation.